2008
DOI: 10.1016/j.mee.2008.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of narrow porous SiOCH trenches using a TiN hard mask

Abstract: For the next technological generations of integrated circuits, the traditional challenges faced by etch plasmas (profile control, selectivity, critical dimensions, uniformity, defects, ...) become more and more difficult, intensified by the use of new materials, the limitations of lithography, and the recent introduction of new device structures and integration schemes. Particularly in the field of the interconnect fabrication, where dual-damascene patterning is performed by etching trenches and vias in porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
(37 reference statements)
0
32
0
1
Order By: Relevance
“…4 From the 45 nm interconnect-technology node, the introduction of porous ultralow-k ͑ULK͒ materials is mandatory in order to compensate for the increase in metal resistance. An important problem of current technologies is that electric signal propagation through metal interconnects is delayed by the resistance ͑R͒ of the metal lines and the capacitance ͑C͒ between adjacent metal lines.…”
Section: Introductionmentioning
confidence: 99%
“…4 From the 45 nm interconnect-technology node, the introduction of porous ultralow-k ͑ULK͒ materials is mandatory in order to compensate for the increase in metal resistance. An important problem of current technologies is that electric signal propagation through metal interconnects is delayed by the resistance ͑R͒ of the metal lines and the capacitance ͑C͒ between adjacent metal lines.…”
Section: Introductionmentioning
confidence: 99%
“…10 They also provide a better selectivity with SiO 2 than F-based plasmas. 12 In addition, TiF x species formed during F-based etching processes may form residues when they react with water in clean room atmosphere. 13 It is also reported that BCl 3 plasmas can form nonvolatile BN x compounds on surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, low etching selectivity (ES), severe faceting, and low-k damage are common problems for pattern transfer processes using SiC and SiO 2 masks. [1][2][3] In this study we investigated basic con-siderations, etching mechanisms, and erosion properties of Ti metal hardmasks for pattern transfer into low-k materials using fluorocarbon (FC)/Ar plasmas. The most promising hard mask candidates are metallic masks such as Ti, TiN, Ta, and TaN.…”
Section: Introductionmentioning
confidence: 99%